205k views
0 votes
Given f(x) = 7x - 4 and g(x) = -3x + 2, find (f+g)(x)​

User Jabongg
by
4.8k points

2 Answers

3 votes

Answer:


\Large \boxed{(f + g)(x) = 4x - 2}

Explanation:

We have two functions.

f(x) = 7x - 4

g(x) = -3x + 2

To find (f+g)(x), we have to find the sum of f(x) and g(x).

(f+g)(x) = f(x) + g(x)

(f + g)(x) = 7x - 4 + -3x + 2

Combining like terms.

(f+g)(x) = 7x - 3x - 4 + 2

(f + g)(x) = 4x - 2

User Inspector Squirrel
by
5.4k points
1 vote

Answer:


(f+g)(x) = 4x - 2

Explanation:

f(x) = 7x - 4

g(x) = -3x + 2

To find (f+g)(x) add g(x) to f(x)

That's


(f+g)(x) = 7x - 4 + (- 3x + 2) \\ = 7x - 4 - 3x + 2 \\ = 7x - 3x - 4 + 2

We have the final answer as


(f+g)(x) = 4x - 2

Hope this helps you

User Mamrezo
by
5.9k points